Association between polycyclic aromatic hydrocarbons and thyroid function among males and females: data from NHANES 2007–2008. Issue 4 (3rd July 2016) - Jain, Ram B.
Abstract: The objective of this study was to evaluate the association between thyroid function and exposure to selected polycyclic aromatic hydrocarbons (PAH) among those aged ≥ 20 years. Thyroid variables considered for evaluation were thyroid-stimulating hormone, free and total serum thyroxine (FT4, TT4), free and total triiodothyronine (FT3, TT3), and thyroglobulin. PAH metabolites in urine for which data were analyzed were 1-hydroxynaphthalene, 2-hydroxynaphthalene, 2-hydroxyfluorene, 3-hydroxyfluorene, 9-hydroxyfluorene, 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, 3-hydroxyphenanthrene, and 1-hydroxypyrene. Using data from 2007 to 2008 National Health and Nutrition Examination Survey, regression models with logs of thyroid variables as dependent variables and PAH exposure, age, race/ethnicity, iodine sufficiency, smoking status, and others as independent variables were fitted. For females, increased levels of 2-hydroxynapthalene, 2-hydroxyphenanthrene, and 1-hydroxypyrene were associated with elevated levels of TT3. For males, increased levels of 1-hydroxyphenanthrene, 2-hydroxyphenanthrene, and 9-hydroxypyrene were associated with decreased levels of FT4.